Mapping teacher wellbeing in Slovakia: insights into resilience, relationships, and support needs - Janik Blaskova, Lenka; Winter, Liz (Frontiers in Education, 2025)
IntroductionThis study explores subjective wellbeing, resilience, and sources of support in the teaching profession, which sits at the heart of communities and society. Teachers need to manage their own wellbeing while playing a critical role in fostering young people’s wellbeing, equipping them for the challenges of the present and future. Slovakia offers an underexplored and critical context for this study, as its education system is in the early stages of recognising the importance of teacher wellbeing and lacks systematic supports for state employees. Additionally, the nation is uniquely positioned within a geopolitical landscape that intensifies stressors on its population.MethodsWe administered a brief online survey to a nationwide sample of teachers in Slovakia (n = 884). Rather than collapsing wellbeing into a single metric, we apply a simple theoretical model that distinguishes self-perceived competence and affect, providing a more comprehensive representation of teacher wellbeing.ResultsOur findings reveal distinct patterns based on gender and years of service in how teachers experience hedonic wellbeing (happiness and satisfaction) and eudaimonic wellbeing (optimal functioning and meaningfulness). Relationships—both within and beyond the profession—emerge as critical determinants of wellbeing, surpassing formal support structures in importance.DiscussionThese results inform recommendations for professional development initiatives grounded in a national perspective, with the potential to enhance teacher support networks and address systemic gaps. By mapping teachers’ social worlds, this study opens pathways for targeted interventions to improve the wellbeing of educators in Slovakia and beyond.